(3JGQjN GdMQcI GdhWfjI ef GdEMJdGd Edi GdESJbdGd (B/s - (3Hf Ndja, YHO GdhgGHs ((3GdLRGFQ (B:s (3OGQ WdjWdI ,s, 2009)
(3JGQjN GdMQcI GdhWfjI ef GdGMJdGd Gdi GdGSJbdGd jcJSj GgejI Ydi GdGbd dSHHjf GdGhd(B: (3Gfg HMK aj JGQjN GdLRGFQ ajg LeY deGOI YdejI ZRjQI JajO GdHGMK HGdOQLI GdGhdi h GdbGQF HTcd YGe h GdKGfj(B: (3Gfg Yed bOe aj Tcd efgLj efXe djchf YhfG dWdHI GdYdhe GdSjGSjI aj eMGVQGJge GdNGUI HJGQjN GdLRGFQ s
(3HjHdjhZQGajG(B:(3U(B.259-264 (3edGMXI (B: 239-257s
Keywords: (3GdLRGFQs; (3GdMQcI GdhWfjIs; (3JGQjNs